Fabrication and static compression test of hybrid magnetorheological elastomer-fluid for vibration control application - Jaafar M.F.; Ahmad N.A.; Razali Z.I.; Mohamad A.F.; Zulkiffli M.A.I. (American Institute of Physics Inc., 2023)
Magnetorheological elastomer (MRE) and magnetorheological fluid (MRF) are widely known as the class of smart materials which contained micron-sized ferromagnetic particles that can reversibly tune the mechanical properties of damping and stiffness coefficient respectively in the presence of magnetic field. However, the current MR technology of MRE and MRF are working individually in addressing both mechanical properties. This study is concerned with investigation on the hybrid MRE-F which incorporates both MRE and MRF as a single system that can work on the stiffness and damping variability simultaneously. To prove the excellent performance of hybrid MRE-F, this study is done to compare the static behavior of all type of elastomers: Hybrid MRE-F, MRE and passive elastomer in compression mode. In most cases, the performance of all elastomer types is increasing with the increasing percentage of ferromagnetic particles contained in the elastomer. The result reported on the static performance of hybrid MRE-F is affected not only by the type and volume percentage of the ferromagnetic particles, but also the type of elastomer and the strength of magnetic field applied in addressing the stiffness. Although hybrid MRE-F is claimed to be able to change its stiffness and damping properties simultaneously, its performance is less significant when compared even to the passive elastomer if the volume percentage of ferromagnetic particles contained in the silicone matrix falls below 30 %. The results observed in this research would be useful for vibration control in wide range of engineering application such as engine mounting system. 2020 Author(s).